Generation of human excitatory forebrain neurons by cooperative binding of proneural NGN2 and homeobox factor EMX1 - Ang, Cheen Euong; Olmos, Victor Hipolito; Vodehnal, Kayla; Zhou, Bo; Lee, Qian Yi; Sinha, Rahul; Narayanaswamy, Aadit; Mall, Moritz; Chesnov, Kirill; Dominicus, Caia S.; Südhof, Thomas C.; Wernig, Marius (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Generation of defined neuronal subtypes from human pluripotent stem cells remains a challenge. The proneural factor NGN2 has been shown to overcome experimental variability observed by morphogen-guided differentiation and directly converts pluripotent stem cells into neurons, but their cellular heterogeneity has not been investigated yet. Here, we found that NGN2 reproducibly produces three different kinds of excitatory neurons characterized by partial coactivation of other neurotransmitter programs. We explored two principle approaches to achieve more precise specification: prepatterning the chromatin landscape that NGN2 is exposed to and combining NGN2 with region-specific transcription factors. Unexpectedly, the chromatin context of regionalized neural progenitors only mildly altered genomic NGN2 binding and its transcriptional response and did not affect neurotransmitter specification. In contrast, coexpression of region-specific homeobox factors such as EMX1 resulted in drastic redistribution of NGN2 including recruitment to homeobox targets and resulted in glutamatergic neurons with silenced nonglutamatergic programs. These results provide the molecular basis for a blueprint for improved strategies for generating a plethora of defined neuronal subpopulations from pluripotent stem cells for therapeutic or disease-modeling purposes.